Comprehensive Sexual Education in the English pronunciation classroom - Huarte Cavassa, Luciana Aimé (2017)
In 2006, the Comprehensive Sexual Education law was sanctioned in Argentina. Embracing all public and private educational environments, this law requires sexual education to be included cross-curricularly. It also states that the information transmitted needs to be up-to-date, promote gender equality and inclusion, and be applied according to the age and socio-economic background of the group members. What is more, it encourages teachers to consider students not as a homogeneous group but as diverse, cognitive, emotional, social and cultural individual beings. Since it was sanctioned, the law has fostered the educational community’s re-evaluation and renewal of teaching practices in different contexts. As students of the National University of La Pampa, we have witnessed this ongoing process in some of the subjects we have attended. However, we felt that in most of the subjects focused on pronunciation this re-evaluation and renewal was still lacking systematicity. In addition to our experience as students, we also collaborate as student assistants in the subject Phonetics and Phonology I. This is a teaching subject in charge of Mgr. Lilián Inés Ariztimuño, in which students who have successfully passed it are offered the possibility to participate in the process of planning the lessons. In this way, they are able to learn from the teachers in charge of the subject about the inner functioning of a university subject –i.e. which is the criteria and the pedagogical purpose followed when designing activities, lessons and exams, what to take into account when assessing learners, how to use different tools and different pedagogical approaches. Thus, while helping with the revision of the existent teaching materials as part of our contribution as student assistants of the subject, we suggested to take into consideration the requirements of the Comprehensive Sexual Education law. In this paper, we will share our experience adjusting and creating new materials as well as the preliminary outcomes after taking these materials to the classroom.